2021
DOI: 10.1111/jbi.14083
|View full text |Cite
|
Sign up to set email alerts
|

Environmental correlates of taxonomic and phylogenetic diversity in the Atlantic Forest

Abstract: Aim: There is little consensus on which environmental variables are best at predicting multiple dimensions of diversity. We ask whether there are common environmental correlates of diversity, despite ecological differences, across nine clades of plants and animals distributed along a single rainforest domain. For that, we compare the environmental correlates of species richness, phylogenetic diversity, and phylogenetic endemism.Location: Brazilian Atlantic Forest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 68 publications
(97 reference statements)
0
19
1
Order By: Relevance
“…The results showed that current precipitation, and precipitation stability over the past 120 kyrs, are strongly correlated with species richness and phylogenetic diversity. However, our results are less homogenous across groups when phylogenetic endemism is considered (Paz et al 2020(Paz et al , 2021. 8.…”
contrasting
confidence: 65%
“…The results showed that current precipitation, and precipitation stability over the past 120 kyrs, are strongly correlated with species richness and phylogenetic diversity. However, our results are less homogenous across groups when phylogenetic endemism is considered (Paz et al 2020(Paz et al , 2021. 8.…”
contrasting
confidence: 65%
“…The support for this congruence comes from the marked environmental differences accumulated between north and south of AF due to climatic and refugia dynamism (Carnaval et al, 2014), added to a complex topography, where past landscape changes driven by climatic fluctuations from old periods, not only Pleistocene, could have different effects on species diversification (Thomé et al, 2010(Thomé et al, , 2012(Thomé et al, , 2014Leite et al, 2016). Even though D. elegans is a common species that occupies natural and human-impacted ecosystems, environmental differences along the AF and the cold temperatures during different periods could also have caused a reduction of gene flow between north and south populations, helping drive the genetic differences present in this study (see Paz et al, 2020).…”
Section: Discussionmentioning
confidence: 79%
“…Diversity Metrics: Species Richness, Diversity, Endemism Phylogenetic Maps, and Environmental Variables Importance Species richness, phylogenetic diversity, and phylogenetic endemism were calculated by superimposing the distribution maps of all species using the R package phyloregion (Daru et al, 2020b). In order to avoid overestimation of the diversity metrics, we created alpha hulls with the R package rangeBuilder (Davis Rabosky et al, 2016) and following (Paz et al, 2021). Briefly, we used occurrence data available for all species (54,392 georeferenced records) that had more than 10 locality points, a dynamic selection of alpha for each species, and an alpha that varied in steps of 1 (Meyer et al, 2017).…”
Section: Species Distribution Modeling and Environmental Variables Importancementioning
confidence: 99%
“…We also used four machine learning algorithms to generate correlative models and then we created an ensemble prediction of each diversity metric to identify the environmental variables that best explain them (Paz et al, 2021). The algorithms used were: Random Forests (Liaw and Wiener, 2002), Neural Network (Venables and Ripley, 2002), Support Vector Machines (Karatzoglou et al, 2004), andGLM (McCullagh andNelder, 1989).…”
Section: Species Distribution Modeling and Environmental Variables Importancementioning
confidence: 99%